Can the ecosystem services concept help in enhancing the resilience of land-sea social-ecological systems?. (May 2016) - Zaucha, Jacek; Conides, Alexis; Klaoudatos, Dimitris; Norén, Katja
Abstract: The paper analyses the possibility of using the concept of marine ecosystem services to fuel public debate on the evolutionary resilience of land-sea interface regions. It is based on the experience of the interdisciplinary ARCH project-Architecture and roadmap to manage multiple pressures on lagoons (financed by the Seventh Framework Programme of the EU) that researched the development of selected European regions located around estuaries, fjords, and lagoons. The ARCH project aimed at elaborating interdisciplinary management plans for ten land-sea interface regions in the EU. Marine ecosystem services were used in this process and proved their usefulness as a spanning object bringing together different types of interests, expertise, and knowledge in a holistic way. The paper presents different ways of handling marine ecosystem services as a trigger for public debate on resilience in land-sea interface regions. It analyses the strong and weak points of the concept of ecosystem services to this end and suggests some key preconditions for the more conscious, effective use of the concept in daily decision-making processes in land-sea complex social-ecological systems. Graphical abstract: Highlights: Development of land-sea interface regions characterized by complex governance patterns, uncertainty, path dependence. Ecosystem services concept supports public debate on the resilience of such regions. Ecosystem services as a link between the ecological and societal components of socio-ecological systems. Ecosystem services as awareness raising and an educational vehicle. Ecosystem services as a bridging platform between different disciplines and societal groups.